Relationship between makeup and film industry through desired attraction and attraction to manipulate general perception in character design: south korea digital media series - ALGÜL, NEVİN (My University, 2022)
The place of make-up in the characters designed to increase the audience rate and create addiction in the audience; from framing in the film industry; The subject of this research is the possible demands from the make-up industry, along with the existing methods to obtain the desired images, which are thought to affect the general majority, and how these demands can or do lead the industry. Since it is the South Korean Digital Media Drama Industry in question. The. article is also related to South Korean makeup industry brands and brand approaches. Traditional make-up trends, (racial characteristics), skin features, whiteness, eyelashes, and the effect it creates, hair and body makeup will be included in the content of the article as an influencing factor. Keywords: Character Creation, Hair and Body Design, Yellow Skin, Digital Media Series, Eyelashes
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Character Creation; Face Design; Yellow Skin; Make Up; Digital Media Series; Eyelashes